Tinjauan Literatur: Adaptasi Visual Batik Sunda dan Karawang dengan Keterkaitan Gambar Mahluk Bernyawa - Suliastuti, Iftika (Serat Rupa: Journal of Design, 2025)
Visual adaptation is an activity aimed at developing historical values and symbolic meanings of cultural identity. Regional aesthetic visual identity is expressed through the development of decorative motifs. The decorative motifs of Sunda batik reflect the cultural values and traditional identity of the Sundanese community through the combination of stylization, abstraction, and formal shapes. Cultural transformation has led to the emergence of "Modern Sunda" while preserving its characteristic motifs. On the other hand, Karawang batik adapts elements from agricultural activities, transforming stylized paddy plants into unique motifs that reflect the identity of the Karawang community. Visual adaptation is also applied in depicting living beings in batik motifs, as seen in the Rifa’iyah community, where incomplete depictions of living beings are developed, and their techniques are preserved as a tradition to sustain batik-making activities. Furthermore, visual adaptation is applied to products, such as cartoon unicorn designs in abstract stylization, to meet market demands, particularly in Muslim products. This study aims to provide a literature review on visual adaptation of decorative motifs in Sunda and Karawang batik, particularly in relation to the depiction of living beings. The research employs a qualitative Systematic Literature Review (SLR) approach by interpreting previous studies as evidence to provide answers. This research explains the connection between batik motifs and visual adaptation of living beings, aiming to develop activities and aesthetic forms relevant to contemporary times.